Election Omnibus: Efforts to Realize Legal Certainty in General Elections in Indonesia - Baharuddin Riqiey; Miftaqul Janah (Mimbar Keadilan, 2025)
Constitutional Court Decision Number 85/PUU-XX/2022 explicitly states that there is no longer any difference between the Election regime and the Regional Election regime. This decision, in addition to providing legal certainty regarding which institution is authorized to resolve disputes over the results of the Regional Election, on the one hand also creates legal uncertainty itself. The legal uncertainty is regarding the extent to which the Regional Election regime is merged into the Election regime as stated in the decision, whether it is only limited to the principles of implementation and institutions authorized to resolve disputes over results or all of them. On that basis, this study aims to examine and analyze the urgency of forming an omnibus Election law in order to realize legal certainty for Elections in Indonesia. This research is a legal research using a statutory approach, conceptual approach, and case approach. The results of this study indicate that the meaning of merging the Regional Election regime into the Election regime must be interpreted as a whole. Starting from the organizing institution, the principles of implementation, to the institution authorized to resolve disputes over results. So, it is important to form what is called an omnibus Election law. This is because to realize legal certainty; To implement Constitutional Court Decision Number 85/PUU-XX/2022; and To realize a meaningful election.